2015
DOI: 10.1002/cam4.402
|View full text |Cite
|
Sign up to set email alerts
|

Using topical imiquimod for the management of positive in situ margins after melanoma resection

Abstract: The treatment of melanoma in situ (MIS) is controversial with current standard of care being surgical excision with clear margins. Alternative topical therapy with imiquimod has been proposed in recent studies as a possible treatment for MIS. This study aimed to evaluate the use of topical 5% imiquimod as an alternative approach for the treatment of residual melanoma in situ after surgical resection of the primary lesion. A retrospective chart review of all patients treated with topical 5% imiquimod for residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
0
20
0
2
Order By: Relevance
“…Approved by the US Food and Drug Administration (FDA) only for the treatment of superficial basal cell carcinomas, actinic keratosis, and genital warts, it is used regularly as an off‐label alternative therapy for melanoma in situ with mixed, but generally favorable, results . Although limited to case reports and small case series, some recent data have emerged examining the use of imiquimod for the management of residual in situ disease following resection for both in situ and invasive melanoma . One study of 22 patients treated with imiquimod for positive in situ margins following surgical excision for melanoma found that 95% had complete resolution of residual disease without recurrence at a mean follow‐up of 24 months .…”
Section: Adjuvant Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Approved by the US Food and Drug Administration (FDA) only for the treatment of superficial basal cell carcinomas, actinic keratosis, and genital warts, it is used regularly as an off‐label alternative therapy for melanoma in situ with mixed, but generally favorable, results . Although limited to case reports and small case series, some recent data have emerged examining the use of imiquimod for the management of residual in situ disease following resection for both in situ and invasive melanoma . One study of 22 patients treated with imiquimod for positive in situ margins following surgical excision for melanoma found that 95% had complete resolution of residual disease without recurrence at a mean follow‐up of 24 months .…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…Although limited to case reports and small case series, some recent data have emerged examining the use of imiquimod for the management of residual in situ disease following resection for both in situ and invasive melanoma . One study of 22 patients treated with imiquimod for positive in situ margins following surgical excision for melanoma found that 95% had complete resolution of residual disease without recurrence at a mean follow‐up of 24 months . Although meager, these reports are promising, demonstrating the potential benefit of imiquimod as an adjuvant therapy to improve local control following resection for melanoma, and underscore the need for further investigation.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…However, this approach suffers from the inability to examine pathologic tissue for occult invasive melanoma. 13–14 …”
Section: Discussionmentioning
confidence: 99%
“…Although surgical excision remains the standard treatment for skin cancer lesions, nonsurgical and pharmaceutical strategies can also achieve acceptable cure rates (Berking et al, ; V. F. M. Carvalho et al, ). Nonsurgical approaches have been recommended for superficial and/or diffuse nonmelanoma lesions, management of positive in situ margins after melanoma resection and melanoma in situ subtypes on chronically sun‐exposed elderly individuals, among other uses (Pandit, Geiger, Ariyan, Narayan, & Choi, ; Swetter, Chen, Kim, & Egbert, ). Factors that influence treatment decisions include the affected area, possibility to operate and the patient age (Berking et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that influence treatment decisions include the affected area, possibility to operate and the patient age (Berking et al, ). Compared with systemic treatment, topical, self‐administered alternatives are highly desirable for drug localization in the tumor lesion, reducing systemic exposure and the incidence of associated adverse effects (Pandit et al, ; Swetter et al, ).…”
Section: Introductionmentioning
confidence: 99%